23 1/2 lies : thrillers - Patterson, James, 1947-; Paetro, Maxine; Bourelle, Andrew; Estleman, Loren D.; Patterson, James, 1947-; Patterson, James, 1947- (New York : Grand Central Large Print, 2023)
23 1/2 lies: Lindsay Boxer's estranged father is gunned down execution-style, and her investigation uncovers life-altering truths.
Fallen Ranger: To Rory Yates, being a Texas Ranger means absolute loyalty to the badge. But he's put through the ultimate test when an armored car robbery suspect might be an ex-Ranger gone rogue.
Watch your back: When a starving artist is paid to expose his client's cheating wife, can he paint the picture that will save his own life?
23 1/2 lies / James Patterson and Maxine Paetro -- Fallen Ranger / James Patterson and Andrew Bourelle -- Watch your back / James Patterson and Loren D. Estleman.
"Enjoy three heart-racing thrillers from the New York Times bestselling master of suspense"--Provided by publisher.
Keywords: Boxer, Lindsay -- (Fictitious character) -- Fiction; Texas Rangers -- Fiction; Women's Murder Club (Imaginary organization) -- Fiction; Murder -- Investigation -- Fiction; Automobile theft -- Fiction; Artists -- Fiction; Large print books